Communicative Language Teaching Method: Analysis of Teachers' Prophetic Problems At Daar El-Nayl Islamic Boarding School Cilebut Bogor - Harared, Nico; Hadi, Irfan; Saputri, Nia Liska (Edumedia Solution, 2023)
In learning English, speaking ability is essential aspect, especially for teachers, especially pronunciation. Implementation in the classroom, the teacher is expected to be a good facilitator and motivator with the hope that later students will have the ability to communicate smoothly and their enthusiasm for learning will continue to increase. One teaching method that can be applied is Communicative Language Teaching (CLT). The purpose of this research to increase the teacher's motivation, creativity, exploration of the teacher's English communication skills. Besides that, through this teaching method it is hoped that it can add new experiences for teachers. This research is classroom action research conducted at the Daar El-Nayl Cilebut Islamic Boarding School, Bogor. There are a total of 4 teachers, they are the objects in this study. Data collection was carried out by observing and recording the value of each research stage. The results of the study showed that there was an increase in the ability to communicate in the pronunciation of English vocabulary which could be seen from the increase in the average score.Â